An introduction to dynamics of colloids - Dhont, Jan K. G. (Studies in interface science, 1996)
One of the few textbooks in the field, this volume deals with several aspects of the dynamics of colloids. A self-contained treatise, it fills the gap between research literature and existing books for graduate students and researchers. For readers with a background in chemistry, the first chapter contains a section on frequently used mathematical techniques, as well as statistical mechanics. Some of the topics covered include: & bull; diffusion of free particles on the basis of the Langevin equation & bull;the separation of time, length and angular scales; & bull; the fundamental Fokker-Planck and Smoluchowski equations derived for interacting particles & bull; friction of spheres and rods, and hydrodynamic interaction of spheres (including three body interactions) & bull; diffusion, sedimentation, critical phenomena and phase separation kinetics & bull; experimental light scattering results. For universities and research departments in industry this textbook makes vital reading.